PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP PRAKTIK INCOME SMOOTHING - Sari, Aning Yunita (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to examine the influence of company size, profitability and leverage to the income smoothing practice. The population is manufacturing companies which are listed in Indonesia Stock Exchange from 2009 to 2012. 36 companies have been selected by using purposive sampling method. The data is obtained through website www.idx.co.id. The data analysis is using logistic regression. The result of simultaneous test shows that company size, profitability, and leverage have an influence to the income smoothing practice. The partial examination shows that company size and profitability have significant influence to the income smoothing practice. The leverage has no significant influence to the income practice smoothing.Keywords: Income Smoothing, Company Size, Profitability, and Leverage